Physical chromosome mapping of repetitive DNA sequences in Nile tilapia Oreochromis niloticus: Evidences for a differential distribution of repetitive elements in the sex chromosomes - Ferreira, Irani A. [UNESP]; Martins, Cesar [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Repetitive DNAs have been extensively applied as physical chromosome markers on comparative studies, identification of chromosome rearrangements and sex chromosomes, chromosome evolution analysis, and applied genetics. Here we report the characterization of repetitive DNA sequences from the Nile tilapia (Oreochromis niloticus) genome by construction and screening of plasmid library enriched with repetitive DNAs, analysis of a BAC-based physical map, and hybridization to chromosomes. The physical mapping of BACs enriched with repetitive sequences and C(o)t-1 DNA (DNA enriched for highly and moderately repetitive DNA sequences) to chromosomes using FISH showed a predominant distribution of repetitive elements in the centromeric and telomeric regions and along the entire length of the largest chromosome pair (X and Y sex chromosomes) of the species. The distribution of repetitive DNAs differed significantly between the p arm of X and Y chromosomes. These findings suggest that repetitive DNAs have had an important role in the differentiation of sex chromosomes. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: cytogenetics; fish; genome; in situ hybridization; sex chromosomes